Issue of Unethical Advertisement: Medico-legal Issues in India-A Case Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
The Division Bench of Bombay High Court observed that a true professional who goes by the rules is competent and mature enough to understand that if any action has to be taken against his peers, he should not hesitate and while dealing with them, he should act fairly and in a just manner. This hope and trust are believed by the Council. It was submitted that the MMC lacked jurisdiction to entertain and try the complaint. It is a complaint alleging breach of medical ethics and such allegations pertaining to non-observance of Indian Medical Council (Professional Conduct, Etiquette and Ethics) Regulations, 2002. If any breach or non-observance of such regulations is alleged and if that is required to be inquired into, then, it is only the Medical Council of India which can initiate the necessary action. The MMC, in terms of its powers under the MMC Act, cannot initiate and conduct any inquiry. [Para 38]. The said order on the face of it is perverse and bad in law. The purported order of the Council has been passed as an afterthought and in great haste only to adopt arm twisting methods against the petitioners. Inviting Division Bench attention to the notice of charges at page 67 of the paper book, it is submitted that there is no reference therein to clause 6.4 of the Regulations. There is only reference to clause 6.1 (advertisement) and clause 6.1.2. The order, therefore, does not restrict itself only to the charges/memo of the same but travels much beyond it. Apart from the complaint from the Advertising Council, the Notice of charges refers to some other material but which was never disclosed to the Petitioners and not made available otherwise. It is stated that there is a gross violation of the principles of natural justice and procedural rules under the MMC Act, as the notice only gives seven days to put in a written statement of defence by the petitioners. This time was wholly inadequate and insufficient. In these circumstances, the impugned orders deserve to be set aside. Division Bench of Bombay High Court by a brief order dated 29.04.2016, directed as under: “For the reasons separately recorded, we reduce the period of suspension from 13th April, 2016 till 30th April, 2016, both days inclusive. The petitioners can commence their practice from 1st May, 2016.”
Keywords: Medical register; High court; Maharashtra medical Council; Registrar; Penalty